Praktik pemberian makan terhadap kejadian kurus pada anak baduta - Fithia Dyah Puspitasari; Mei Neni Sitaresmi; Susetyowati Susetyowati; Iram Barida; Kartika Handayani (Jurnal Gizi Klinik Indonesia, 2018)
Background: Wasting is an acute malnutrition form that interrupts immune function, prolong duration of infection and in the end increase mortality risk of children. It is not clear yet which risk factor leading to wasting, simply because wasting-suspected risk factors were also involved in another kind of malnutrition such as stunting and underweight.Objective: To determine whether infant and young child feeding practices is risk factor for wasting in under two year children.Method: This research was mix method research which used matching case control design for quantitative research and focus group discussion to gather information in qualitative research. Case were wasting children age 3-23 months old (z-score WHZ <-2 SD) while control were non-wasting children age 3-23 months old (z-score WHZ ≥-2 SD). This research involved 106 under-two years old children and 14 nutritionist from 14 community health center which randomly chosen. Control group was matched by age and socio economic to case group.Results: Case group had more proportion of inappropriate feeding practices (26.41%% vs 20.75%). More than half respondent failed to meet Indonesian recommended dietary allowance for energy (57.55%). Inappropriate infant and young child feeding practice significantly did not increased risk of wasting in under two children at Yogyakarta (OR=1.4; 95% CI:0.62-3.36; p=0.523). Nutritionist from community health center focused in consultation and counseling in effort to increase infant and young child feeding practice.Conclusion: Feeding practices in under-two children in Yogyakarta was already good. Infant and young child feeding practice was not risk factor for wasting in under two years old children at Yogyakarta.